Laundry bar composition
Patent Information
- Application Number
- CN202180080632.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-10
- Filing Date
- 2021-12-09
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-12-09
AI Technical Summary
另一方面,使用不溶性填料倾向于增加组合物的粘度,导致加工困难
[0112]根据本发明的洗衣皂条组合物具有0.8至1.3,优选1.01至1.15克/立方米的密度。本发明的一个显著优点是它允许掺入水而不会显著影响条的密度。本发明的条密度类似于具有较高脂肪酸皂量的常规洗衣皂条组合物的密度。
Smart Images

Figure BDA0004257887490000271 
Figure BDA0004257887490000281 
Figure BDA0004257887490000282
Abstract
Description
Invention Field
[0001] This invention relates to laundry compositions in shaped solid form for direct application to fabrics. More specifically, it relates to soap compositions in strip or tablet form suitable for hand washing fabrics. Background of the Invention
[0003] Laundry detergent compositions, such as laundry strips, powders, gels, and tablets, are used for handwashing clothes at ambient temperatures. Laundry strips designed for handwashing fabrics are formulated to provide effective fabric cleaning, acceptable foaming properties, low abrasion rate, good stiffness, durability, and low staining performance. Laundry strip compositions may include soap, synthetic detergents, or a combination of soap and synthetic detergents as the primary detergency surfactant. In some parts of the world, soap-based laundry strips are preferred for washing fabrics.
[0004] Soap is typically made from animal and plant-based fats and oils, which contain relatively high levels of water. Laundry bars that use soap as their sole or primary surfactant also usually contain relatively high levels of water. This high water content in laundry soap bars makes them soft and difficult to use.
[0005] Consumers of laundry bars typically want sturdy bars that allow for vigorous scrubbing of clothing without excessively abrading the material. Soap bars intended for washing fabrics need to be sturdier than those intended for cosmetic purposes in order to effectively remove dirt from fabrics during the scrubbing process.
[0006] To achieve the desired firmness, laundry soap bar manufacturers dry excess water from the soap raw materials—an expensive and often inefficient technique. When mass-producing bars, drying excess water from the finished laundry bars is both time-consuming and costly. Since soap-based laundry compositions are commonly used in emerging world economies, cost reduction is a crucial consideration in formulating these bars.
[0007] Typically, laundry soap bar compositions comprise 60% by weight or higher levels of soap to provide a suitable combination of cleaning performance, foaming ability, and firmness. Soap is derived from triglycerides, which are becoming increasingly expensive. Therefore, manufacturers are seeking ways to utilize soap more efficiently in soap bars.
[0008] A particular desire is to reduce the soap content in laundry soap bar compositions without altering cleaning performance, firmness, and sensory properties. Several different techniques have been explored in the past to reduce the soap content in laundry soap bar compositions.
[0009] One strategy to reduce the overall soap content is to increase the water content. However, attempting to increase the water content in soap bars results in soap bars that are soft and sticky, and the composition is extremely difficult to process into bars using conventional equipment. Generally, increasing the water content of laundry bars causes them to tend to shrink during storage, leading to stress cracking.
[0010] Another possible way to reduce soap content is to include fillers. However, using both soluble and insoluble fillers in laundry soap bar compositions can have some adverse effects. Using soluble fillers (such as polyols) tends to negatively impact foaming, bar stiffness, and increase wear rate. On the other hand, using insoluble fillers tends to increase the viscosity of the composition, leading to processing difficulties.
[0011] When soap content is minimized, the use of synthetic (such as anionic) surfactants remains another way to compensate for performance loss and foaming loss.
[0012] WO 96 / 35772A1 (P&G, 1996) discloses a laundry soap bar composition comprising a combination of soap and a synthetic anionic surfactant to provide the desired bar firmness.
[0013] Alternatively, soap bar compositions with lower soap content can be prepared by incorporating a structured system into the laundry soap bar.
[0014] One such example includes the laundry bar composition disclosed in WO 2008 / 071561 A1 (Unilever), which discloses a low-TFM soap bar with improved firmness. The soap bar composition comprises 30% to 70% soap and a structured system prepared by mixing the soap with sodium silicate and a water-soluble calcium compound to produce in-situ formed calcium silicate.
[0015] IN187129 (Hindustan Lever Ltd. 1997) discloses a detergent strip for laundry, having a low soap content and in-situ formed aluminosilicate structuring agent. It discloses that the structuring agent aluminosilicate is formed in situ from soluble aluminum salts and silicates or sodium aluminate and basic silicates.
[0016] Although several methods are known to provide laundry soap bars with lower soap content that offer the desired firmness, good cleaning performance, and maintain the desired sensory properties, there is still a need for improved laundry soap bar compositions with high water content (which is maintained in the finished soap bar composition) that, when such compositions have low soap content and minimal or no synthetic surfactants, still offer good firmness and cleaning performance while maintaining good user performance.
[0017] Therefore, one object of the present invention is to provide a laundry soap bar composition having a low soap content while maintaining good user performance and bar firmness.
[0018] Another object of the present invention is to provide a laundry soap bar composition with good cleaning performance.
[0019] Another object of the present invention is to provide a laundry soap bar composition having a low soap content and a high water content, wherein a relatively high water content is maintained in the finished bar composition, and the bar composition retains its shape and integrity and is suitable for consumer use.
[0020] Another object of the present invention is to provide a method for preparing a laundry soap bar composition having a low soap content and a high water content.
[0021] Another object of the present invention is to provide a low TFM laundry soap bar composition that, in addition to being easily extruded and stamped, does not compromise the integrity of the bar and provides desired sensory properties such as high foaming and low pasteiness. Invention Overview
[0023] The inventors have discovered that by introducing a balanced combination of preferably in-situ generated silica gel and a silicate structuring agent selected from calcium silicate, aluminum silicate, sodium aluminosilicate, or mixtures thereof, a laundry soap bar composition can be provided that has a low fatty acid soap content and a high water content while still maintaining satisfactory bar stiffness and sensory properties. This laundry soap bar composition also provides good cleaning performance, good foaming properties, and good fragrance release.
[0024] According to a first aspect, the present invention discloses a laundry soap bar composition comprising:
[0025] i) 30% to 55% by weight of fatty acid soaps;
[0026] ii) 10% to 15% by weight of silica gel having a specific surface area of at least 25 square meters per gram;
[0027] iii) a silicate structuring agent, wherein the silicate structuring agent is selected from calcium silicate, aluminum silicate, sodium aluminosilicate, or mixtures thereof; and
[0028] iv) 30% to 45% water by weight.
[0029] According to a second aspect of the present invention, a method for preparing the laundry soap bar composition of the first aspect is disclosed, comprising the following steps:
[0030] i) Neutralize one or more fatty acids or fats with an alkaline neutralizing agent to obtain fatty acid soaps;
[0031] ii) Acidify basic silicates to form silica gel in situ;
[0032] iii) Add silicate structuring agents and water to form a dough-like substance; and
[0033] iv) The resulting dough-like substance is converted into a shaped laundry soap bar composition.
[0034] The laundry soap bar composition contains 30% to 55% by weight of fatty acid soap and 30% to 45% by weight of water.
[0035] According to a third aspect, the present invention discloses the use of silica gel having a specific surface area of at least 25 m² / g, a silicate structuring agent, and 30% to 45% by weight of water in a laundry soap bar composition having 30% to 55% by weight of fatty acid soap for providing improved bar performance, wherein the silicate structuring agent is selected from calcium silicate, aluminum silicate, sodium aluminosilicate, or mixtures thereof.
[0036] According to another aspect, the present invention discloses the use of silica gel having a specific surface area of at least 25 m² / g, a silicate structuring agent, and 30% to 45% by weight of water in a laundry soap bar composition having 30% to 55% by weight of fatty acid soap for providing improved aroma delivery, wherein the silicate structuring agent is selected from calcium silicate, aluminum silicate, sodium aluminosilicate, or mixtures thereof.
[0037] According to another aspect, the present invention discloses the use of silica gel having a specific surface area of at least 25 m² / g, a silicate structuring agent, and 30% to 45% by weight of water in a laundry soap bar composition having 30% to 55% by weight of fatty acid soap for providing improved foaming properties, wherein the silicate structuring agent is selected from calcium silicate, aluminum silicate, sodium aluminosilicate, or mixtures thereof.
[0038] The term "soap bar" refers to a laundry composition in the form of a molded solid. This soap bar is a solid form that retains its shape after manufacturing and during transportation and storage. The term "soap bar" also includes other molded laundry bar compositions, such as cakes or sheets. The molded solid is preferably formed via a casting route or an extrusion route, more preferably via an extrusion route.
[0039] These and other aspects, features, and advantages will become apparent to those skilled in the art upon reading the following detailed description and appended claims. For the avoidance of doubt, any feature of one aspect of the invention may be used in any other aspect of the invention. The word “comprising” is intended to mean “including” but not necessarily “consisting of” or “made of”. In other words, the listed steps or options need not be exhaustive. Note that the examples given in the following description are intended to illustrate the invention and not to limit the invention to these examples alone. Similarly, unless otherwise stated, all percentages are weight / weight percentages. Unless in operational and comparative examples, or where expressly stated otherwise, all figures in this specification and claims indicating the amount of material or reaction conditions, physical properties of the material, and / or uses should be understood to be modified with “about”. Numerical ranges expressed in the form of “from x to y” are understood to include both x and y. When multiple preferred ranges are described in the form of “from x to y” for a particular feature, it should be understood that all ranges combining different endpoints are also considered. Invention Details
[0041] According to a first aspect of the present invention, a laundry soap bar composition is disclosed, comprising 30% to 55% by weight of fatty acid soap, silicate structuring agent, silica gel, and 15% to 45% by weight of water.
[0042] Fatty acid soap
[0043] According to a first aspect of the invention, the disclosed laundry soap bar composition comprises 30% to 55% by weight of fatty acid soap.
[0044] The term fatty acid soap refers to salts of carboxylic acid fatty acids. These compounds include common alkali metal soaps of carboxylic acid fatty acids, such as sodium, potassium, and ammonium salts. Soaps can be made by the direct saponification of fats and oils or by the neutralization of free fatty acids. Particularly useful are sodium and potassium salts derived from mixtures of fatty acids from coconut oil, tallow, fish oil, soybean oil, and palm oil, such as sodium and potassium tallow soaps. Sodium soaps are typically used in the compositions of this invention, but soaps can also be selected from potassium, magnesium, or triethanolamine soaps. Soaps usable in this invention are well-known alkali metal salts of natural or synthetic aliphatic (alkane or alkene) acids having 8 to 22 carbon atoms, preferably 10 to 18 carbon atoms. They can be described as alkali metal carboxylates of saturated or unsaturated hydrocarbons having 8 to 22 carbon atoms. Fatty acids can be synthesized, for example by the oxidation of petroleum feedstocks or by the Fischer-Tropsch process.
[0045] The fatty acid soaps according to the invention preferably comprise lauric acid soaps. Lauric acid soaps preferably comprise fatty acid soaps having 8 to 14 carbon atoms. Preferably, these comprise fatty acid soaps primarily derived from C8 to C9. 12 Soaps made from saturated fatty acids (i.e., lauric acid), but may contain small amounts derived from shorter-chain fatty acids (e.g., C). 10 Lauric acid soaps are typically derived in practice from the hydrolysis of nut oils such as coconut oil and palm kernel oil. Lauric acid soaps, with short-chain fatty acid molecules having 8 to 12 carbon atoms, lather rapidly. These are fatty acids or lauric oil (i.e., C8 to C12). 12 Palm kernel oil, coconut oil) and a selected alkali (Na) + and / or K + The saponification products of lauric acid soap. Lauric acid soap is mainly saturated.
[0046] Fatty acid soaps can also include those with a carbon chain length of C. 14 Or longer-chain soaps. Long-chain fatty acid soap molecules preferably include fatty acid soaps having 14 to 22 carbon atoms, more preferably 16 to 22 carbon atoms, and even more preferably 16 to 20 carbon atoms. They can be classified as follows:
[0047] "Stearic acid" soaps contain mainly C-derived... 16 To C 18 Soaps made from saturated fatty acids (i.e., palmitic acid and stearic acid), but may contain lower levels of long-chain fatty acids (such as C). 20 Saturated soaps containing stearic acid. Stearic acid soaps are actually usually derived from triglyceride oils, such as tallow, palm oil, and palm stearin.
[0048] "Oleic acid" soaps are soaps derived from unsaturated fatty acids, primarily oleic acid (C...). 18:1 ), linoleic acid (C 18:2 ), myristone acid (C 14:1 ) and palmitoleic acid (C 16:1 Oleic acid soaps contain small amounts of both longer and shorter chain unsaturated and polyunsaturated fatty acids. In practice, oleic acid soaps are typically derived from the hydrolysis of various triglyceride oils and fats, such as tallow, palm oil, sunflower oil, and soybean oil.
[0049] With C 14 To C 22 Fatty acid soaps containing carbon atoms, more preferably those containing C 14 To C 22Carbon-saturated soaps are insoluble in water and help maintain their structure, but long-chain fatty acid soaps do not readily produce lather. Long-chain fatty acid soap molecules are the saponification products of non-lauric oils (such as stearic acid and oleic acid) with sodium hydroxide (usually containing sodium counterions). Non-lauric acids refer to long-chain saturated (C6O4) fatty acids found in palm oil, palm stearin, and tallow. 16 and C 18 ) and unsaturated (C 18:1 C 18:2 C 18:3 )fatty acid.
[0050] In the laundry soap bar composition according to the invention, it is preferable to have C 14 Or long-chain soap molecules with a larger number of carbon atoms and C 12 The weight ratio between short-chain soap molecules with a number of carbon atoms or less is 85:15 to 98:2, preferably 80:20 to 90:10.
[0051] Preferably, the laundry soap bar composition according to the invention comprises 30% to 55% by weight of fatty acid soap. Preferably, the laundry soap bar composition comprises at least 32% by weight, preferably at least 33% by weight, more preferably at least 34% by weight, and most preferably at least 35% by weight, but generally not more than 50% by weight, more preferably not more than 45% by weight, further preferably not more than 43% by weight, and most preferably not more than 40% by weight of fatty acid soap.
[0052] silicone
[0053] According to a first aspect of the present invention, a laundry soap bar composition containing silica gel is disclosed. The term "silicone gel" herein refers to silica in an amorphous form comprising a specific surface area of at least 25 m² / g.
[0054] Silica gel can be pre-formed or can be generated in situ during manufacturing. It should be understood that silica gel is silicon dioxide in a porous form. Silica gel is an amorphous solid. The partial dipole nature of the Si-O bonds allows silica gel to form hydrogen bonds with water molecules, while the porous nature and large surface area of silica gel enable the material to readily adsorb water. According to embodiments of the invention, metal silicates can be formed in situ during the manufacturing process of the laundry soap bar composition. More preferably, the specific surface area of the silica gel is in the range of 100 m² / g to 1000 m² / g, more preferably 300 to 750 m² / g. Still preferably, the specific surface area is at least 200 m² / g, more preferably at least 300 m² / g, even more preferably at least 400 m² / g, even more preferably 500 m² / g, and most preferably at least 700 m² / g, but generally not exceeding 950 m² / g, even more preferably not exceeding 900 m² / g, still further preferably not exceeding 850 m² / g, even more preferably not exceeding 800 m² / g, and most preferably not exceeding 750 m² / g. The specific surface area of silica gel can be determined using known methods for measuring specific surface area, such as the BET (Brunauer-Emmett-Teller) nitrogen adsorption method.
[0055] Preferably, silica gel is formed in situ through the acidification of an alkali metal silicate. Any metal silicate that can be converted into silica gel is suitable for this invention. For example, alkali metal silicates such as sodium silicate, potassium silicate, lithium silicate, or any combination thereof are suitable for this invention. The alkali metal silicate can be added on its own (in solid form) or in wet form (e.g., slurry or solution). The alkali metal silicate component is preferably sodium silicate, or a combination of sodium silicate and another metal silicate. Sodium silicate is a water-soluble basic inorganic compound and is often sold as an aqueous solution.
[0056] Sodium silicates are often referred to or characterized by the ratio of their basic oxides to silicon dioxide, such as the ratio of Na₂O to SiO₂. The orthosilicate of formula Na₄SiO₄ is the most basic, with a Na₂O to SiO₂ ratio of 2:1. The metasilicate Na₂SiO₃ has a Na₂O to SiO₂ ratio of 1:1. Water-soluble silicates, known as "water glass," have a Na₂O to SiO₂ ratio in the range of about 1:1.5 to 1:3.8. Preferably, the Na₂O to SiO₂ ratio used in this invention is from 1:1.5 to 1:3.0. In preparing silica gel according to this invention, commercially available alkali metal silicates can be used, wherein the ratio of sodium oxide to silicon dioxide can be in the range of 1:0.48 to 1:3.75, preferably 1:1.5 to 1:3.75, and more preferably 1:3.0 to 1:3.5. Examples of silicates suitable for use in this invention are sodium silicate (Na₂O to SiO₂ ratio of 1:3.0), sodium orthosilicate (Na₂O to SiO₂ ratio of 2:1), and potassium silicate (K₂O to SiO₂ ratio of 1:2.50). Preferably, the alkali metal silicate is alkaline.
[0057] Preferably, silica gel is formed in situ by acidifying a basic silicate with a reactant selected from carbon dioxide, alkali metal bicarbonates, or mixtures thereof. The carbon dioxide gas used can be at full strength or diluted with air or other inert gases, such as diluted carbon dioxide gas produced by the combustion of hydrocarbons like propane or butane. Preferably, the bicarbonate is an alkali metal salt, more preferably sodium bicarbonate. Preferably, the basic silicate is water-soluble or water-dispersible. Preferably, silica gel is formed in situ by acidifying the basic silicate with bicarbonate. Preferably, the basic silicate is sodium silicate, and the bicarbonate is sodium bicarbonate. Preferably, the weight ratio of sodium bicarbonate to sodium silicate is in the range of 1:5 to 1:7.
[0058] Within the scope of this invention, silica gel is formed in situ by reacting water-soluble or water-dispersible silicates with organic acids. Preferably, the organic acid is anionic detergent-forming acid. Non-limiting examples of acids are saturated and unsaturated fatty acids whose carbon chains contain about 8 to 22 carbon atoms, such as lauric acid, stearic acid, oleic acid, and linoleic acid. Non-soap detergent-forming acids, such as alkylaryl sulfonic acids, wherein the alkyl group (straight-chain and branched-chain) has a carbon chain length of at least 4 carbon atoms, preferably 10 to 12 carbon atoms, which can form a water-soluble non-soap detergent upon neutralization with an alkali such as sodium hydroxide or potassium hydroxide.
[0059] The degree of polymerization of silicate to silicate is preferably 50% or higher (i.e., a 1:1 ratio), more preferably 60% or higher, even more preferably 70% or higher, even more preferably 80% or higher, still more preferably 90% or higher, even more preferably 95% or higher, and most preferably 99% or higher. Preferably, the alkali metal silicate is completely polymerized into silicate. Preferably, the pore volume of the silicate is 0.4 to 4.4 mL / g, more preferably 0.5 to 1.4 mL / g. The pore volume can be determined using a mercury porosimeter and is measured as the volume of pores with a diameter greater than 25 micrometers.
[0060] Preferably, the laundry soap bar composition according to the invention contains 10% to 15% by weight of silicone. Preferably, the laundry soap bar composition contains at least 10% by weight, preferably at least 10.5% by weight, more preferably at least 11% by weight, and most preferably at least 11.5% by weight, but generally not more than 15% by weight, more preferably not more than 14.5% by weight, further preferably not more than 14% by weight, and most preferably not more than 13% by weight of silicone.
[0061] Silicate structuring agents
[0062] According to a first aspect of the invention, the disclosed laundry soap bar composition comprises a silicate structuring agent. The silicate structuring agent is selected from calcium silicate, aluminum silicate, sodium aluminosilicate, or mixtures thereof.
[0063] The silicate structuring agent is preferably pre-formed or present in situ during the preparation of the laundry soap bar composition. In-situ formation of the silicate structuring agent is preferred.
[0064] Preferably, the composition comprises a further silicate structuring agent selected from sodium silicate, potassium silicate, magnesium silicate, or mixtures thereof. Most preferably, the further silicate structuring agent is sodium silicate, magnesium silicate, or mixtures thereof.
[0065] Most preferably, the further silicate structuring agent is sodium silicate. Sodium silicate comprises compounds having the formula (Na₂O). xCompounds of SiO2. The weight ratio of Na2O to SiO2 can vary from 1:1.5 to 1:3.8. Sodium silicate grades with a ratio from about 1:2 to 1:2.85 are called basic silicates, and sodium silicate grades with a ratio from 1:2.85 to about 1:3.75 are called neutral silicates. Available forms of sodium silicate include sodium metasilicate (Na2SiO3), sodium pyrosilicate (Na6Si2O7), and sodium orthosilicate (Na4SiO4). According to the invention, it is preferred to use basic sodium silicate. Particularly preferred is sodium silicate with a Na2O to SiO2 ratio of 1:2. Sodium silicate is generally obtained as an aqueous solution with a solid content of 40% to 50%, the balance being water. Preferably, the soap bar composition contains 0.01% to 20% by weight, more preferably 2% to 20% by weight, more preferably 2% to 15% by weight, and even more preferably 3% to 10% by weight of sodium silicate based on dry weight.
[0066] The further silicate structuring agent may also be magnesium silicate, preferably hydrated magnesium silicate, in an amount preferably from 0% to 10% by weight of the composition, more preferably from 1% to 5% by weight, and even more preferably from 1% to 3% by weight. Preferably, the further silicate structuring agent is a mixture of sodium silicate and hydrated magnesium silicate.
[0067] Further silicate structuring agents may be selected from in-situ formed borosilicates, boroaluminosilicates, or combinations thereof. In-situ formation of borosilicate structuring agents can be carried out as described in WO 02 / 46341A2 (Unilever, 2002). In-situ formation of aluminosilicates can be carried out as described in GB-A-209 013 and WO 03 / 040283A1 (Unilever, 2003).
[0068] Preferably, the silicate structuring agent is selected from calcium silicate, silicate, aluminum silicate, sodium aluminosilicate, and combinations thereof.
[0069] Preferably, the laundry soap bar composition according to the invention contains 1% to 30% by weight of a silicate structuring agent, and more preferably, the laundry soap bar composition contains 1% to 10% by weight of a silicate structuring agent. Preferably, the laundry soap bar composition contains at least 2% by weight, preferably at least 5% by weight, more preferably at least 8% by weight, and most preferably at least 10% by weight, but generally not more than 25% by weight, more preferably not more than 20% by weight, further preferably not more than 18% by weight, and most preferably not more than 15% by weight of a silicate structuring agent.
[0070] water
[0071] According to the first aspect, the disclosed laundry soap bar composition comprises 30% to 45% by weight, preferably 33% to 40% by weight, of water. The soap bar composition of the present invention is capable of stably retaining a high water content, ranging from 30% to 40% by weight, more preferably at least 32% by weight, further preferably at least 33% by weight, even more preferably at least 34% by weight, and preferably at least 35% by weight, but the water content in the laundry soap bar composition preferably does not exceed 38% by weight, more preferably not more than 36% by weight, and most preferably not more than 35.5% by weight.
[0072] The preferred water content level described above refers to that of freshly made laundry soap bars, where the water content is measured within 8 hours. This amount is referred to as the “initial water content” or “initial water content” of the freshly made laundry soap bar composition, also known as the “nominal water content” or “nominal water content” of the composition. The water present in the bar at room temperature (approximately 25°C) includes “free” water and bound water of crystallization.
[0073] As is well known, soap bars dry out during storage, meaning that water evaporates from the bar when the relative humidity is below the partial vapor pressure of water in equilibrium with the soap bar composition, and this depends on the rate at which water diffuses from the bar. Therefore, depending on the storage method of the bar (type of packaging paper, temperature, humidity, air circulation, etc.), the actual water content of the bar at the time of sampling may differ from the nominal water content of the bar immediately after manufacturing.
[0074] Optional ingredients
[0075] Laundry soap bar composition:
[0076] In addition to the components described above, the laundry soap bar composition of the present invention may contain a variety of optional ingredients. These optional ingredients include, but are not limited to, synthetic surfactants, water-soluble fillers, water-insoluble fillers, organic and inorganic auxiliary materials, alkaline materials, processing aids, small amounts of additives, dyes, electrolytes, and chelating agents.
[0077] Synthetic surfactants:
[0078] Optionally, the laundry soap bar composition of the present invention comprises a synthetic surfactant. Preferably, the synthetic surfactant is a non-soap anionic surfactant, including but not limited to alkali metal and alkaline earth metal salts of higher alkyl aryl sulfonate surfactants, higher alkyl sulfate surfactants, higher fatty acid monoglyceride sulfate surfactants, or mixtures thereof. Examples of mild synthetic surfactants include alkyl glycerol ether sulfonates (AGS), anionic acyl sarcosinates, methyl acyl taurines, N-acyl glutamates, alkyl glucosides, acyl hydroxyethyl sulfonates, alkyl sulfosuccinates, alkyl phosphates, ethoxylated alkyl phosphates, ethoxylated alkyl alcohols, alkyl sulfates, alkyl ether sulfates, methyl glucose esters, protein concentrates, mixtures of alkyl ether sulfates and alkylamine oxides, betaine, sulfobetaine, and mixtures thereof. The synthetic surfactants include alkyl ether sulfates having about 1 to about 12 ethoxy groups, particularly ammonium lauryl ether sulfate and sodium lauryl sulfate. The alkyl chain length of these surfactants is about C8 to C99. 22 C is preferred 10 To C 18 The alkyl moiety of this synthetic surfactant is typically derived from the same natural fatty acid source as fatty acid soaps.
[0079] The compositions of the present invention contain less than 5% by weight, preferably less than 3% by weight, even more preferably less than 1% by weight, and still more preferably less than 0.1% by weight of synthetic surfactants. Preferably, the compositions of the present invention are substantially free of synthetic surfactants. "Substantially free" means that no synthetic surfactants are intentionally added to the laundry soap bar compositions of the present invention. Preferably, the compositions of the present invention contain less than 5% by weight, preferably less than 1% by weight of non-soap anionic surfactants, and most preferably, the soap bar compositions are substantially free of non-soap anionic surfactants. "Substantially free" means that no non-soap anionic surfactants are intentionally added to the soap bar compositions of the present invention.
[0080] Soluble fillers:
[0081] Optionally, the compositions of the present invention include a soluble filler. The soluble filler consists of a polyol (also called a polyhydric alcohol) or a mixture of polyols. A polyol is the term used herein to refer to a compound having a plurality of hydroxyl groups (at least two, preferably at least three) that is highly water-soluble, preferably readily soluble in water. Many types of polyols are available, including but not limited to relatively low molecular weight short-chain polyols such as glycerol and propylene glycol; sugars such as sorbitol, mannitol, sucrose, and glucose; modified carbohydrates such as hydrolyzed starch, dextrin, and maltodextrin; and polymerized synthetic polyols such as polyalkylene glycols, such as polyoxyethylene glycol (PEG) and polypropylene glycol (PPG). Particularly preferred polyols are glycerol, sorbitol, mannitol, and mixtures thereof. The most preferred polyol is glycerol. Preferably, the soap bar composition of the present invention comprises 0% to 10% by weight of the composition, preferably 0.5% to 7.5% by weight, even more preferably 1% to 7% by weight, and most preferably less than 6% by weight of a soluble filler. Preferably, the soap bar composition comprises 0.5 to 5.5% by weight of a polyol, preferably glycerin.
[0082] Organic and inorganic auxiliary materials:
[0083] Non-limiting examples of organic auxiliary materials may include suitable starchy materials, such as natural starch (from corn, wheat, rice, potatoes, cassava, etc.), pregelatinized starch, various physically and chemically modified starches, and mixtures thereof. The term "natural starch" refers to starch that has not been chemically or physically modified, also known as raw starch or natural starch. Organic auxiliary materials may also be particulate materials, including insoluble polysaccharides such as cross-linked or insoluble starch and cellulose, synthetic polymers, or mixtures thereof. The compositions of the present invention comprise less than 5% by weight, preferably less than 3% by weight, even more preferably less than 1% by weight, and even more preferably less than 0.1% by weight of organic auxiliary materials. Preferably, the compositions of the present invention are substantially free of water-soluble organic auxiliary materials. "Substantially free" means that no intentionally added organic auxiliary materials are present in the laundry soap bar compositions of the present invention.
[0084] Non-limiting examples of inorganic auxiliary materials include granular zeolites, calcite, dolomite, feldspar, silica, other carbonates, bicarbonates, and talc. Calcium carbonate (such as calcite), kaolin, silica, and talc are most preferred. Talc is a magnesium silicate mineral with a platy silicate structure and composition of Mg3Si4(OH). 22 It can be obtained in hydrated form. Examples of other optional insoluble inorganic particulate auxiliary materials include aluminates, phosphates, insoluble sulfates, borates, sodium carbonate, calcium carbonate, magnesium sulfate, clay, and combinations thereof. Preferably, the composition is substantially free of starch, talc, and clays such as kaolin.
[0085] The compositions of the present invention comprise 0% to 12% by weight of inorganic auxiliary materials, preferably 2% to 10% by weight, of the laundry soap bar composition. It is also preferred that the inorganic auxiliary materials comprise less than 5% by weight of the composition.
[0086] Alkaline neutralizing agent:
[0087] The alkaline substance used to neutralize the acidic precursor of fatty acid soap active substances is selected from silicates, carbonates, hydroxides, basic aluminum-containing compounds such as aluminates, phosphates, and mixtures thereof. Preferably, the amount of alkaline substance used is at least equal to the stoichiometric amount required to neutralize the precursor of the soap active substance. For the purposes of this invention, particularly preferred alkaline substances for neutralizing detergent active substances are sodium silicate, sodium hydroxide, sodium aluminate, and sodium carbonate.
[0088] Small amount of additives:
[0089] Non-limiting examples of optional small amounts of additives that may be included in the laundry soap bar compositions of the present invention include colorants, preservatives, fragrances, and other polymers, which may be incorporated into the composition up to 10% by weight. Fragrances may optionally be present at a level of about 0.1% to 1.5% by weight of the composition. Any fragrance known to those skilled in the art may be used, and is not limited to fragrance oils or encapsulated fragrance oils.
[0090] Electrolytes:
[0091] Optionally, the compositions of the present invention comprise an electrolyte. The electrolyte according to the present invention comprises a compound that dissociates substantially into ions in water. The electrolyte according to the present invention is not an ionic surfactant. Suitable electrolytes included in the soap-making process are alkali metal salts. Preferred alkali metal salts included in the compositions of the present invention include sodium sulfate, sodium chloride, sodium acetate, sodium citrate, potassium chloride, potassium sulfate, sodium carbonate, and other mono, di, or trisalts of alkaline earth metals. More preferred electrolytes are sodium chloride, sodium sulfate, sodium citrate, and potassium chloride, and particularly preferred electrolytes are sodium carbonate, sodium chloride, sodium citrate, or sodium sulfate, or combinations thereof. Preferably, the electrolyte is sodium carbonate or sodium chloride. To avoid doubt, it needs to be clarified that the electrolyte is a non-soap material. The compositions of the present invention comprise 0.5% to 5% by weight of the composition, preferably 0.5% to 3% by weight, more preferably 1% to 2.5% by weight of the electrolyte. More preferably, the compositions of the present invention have less than 4.2% by weight of the electrolyte, even more preferably less than 3% by weight, and further preferably less than 2% by weight of the electrolyte. Most preferably, the compositions of the present invention do not require any electrolyte.
[0092] Chelating agents:
[0093] Optionally, the compositions of the present invention include a chelating agent. The chelating agent may be selected from, but is not limited to, ethylenediaminetetraacetic acid (EDTA), ethylenedihydroxybisphosphonic acid (EHDP), or mixtures thereof. The chelating agent is preferably present in an amount of 0.01% to 1% by weight. Non-phosphate chelating agents such as methylglycine diacetic acid and its salts are also preferred.
[0094] polymer:
[0095] Optionally, the compositions of the present invention comprise polymers, preferably selected from cationic polysaccharides, cationic copolymers of sugars and synthetic cationic monomers, homopolymers of dimethyl diallyl ammonium chloride, copolymers of dimethyl diallyl ammonium chloride and acrylamide, quaternized vinylpyrrolidone acrylate or methacrylate copolymers of amino alcohols, cationic homopolymers and copolymers derived from acrylic acid and / or methacrylic acid, cationic polymers of polyalkylene imides and ethoxylated polyalkylene imides and mixtures thereof. The cationic polymers include cationic polymers of natural and synthetic origin. Preferably, the cationic polymer is a polymer of dimethyl diallyl ammonium chloride (DMDAAC), comprising homopolymers and copolymers of dimethyl diallyl ammonium chloride (DMDAAC) or mixtures thereof. Preferably, it is a copolymer of dimethyl diallyl ammonium chloride and acrylamide.
[0096] Non-limiting examples of polymers suitable for the laundry soap bar compositions of the present invention include Merquat S, Merquat 550, and Merquat 100 of Lubrizol. Inc., and acrylic copolymers such as Noverite. TM GP250. The laundry soap bar composition according to the invention comprises 0.01% to 5% by weight of a cationic polymer.
[0097] Personal washing soap bar composition:
[0098] The soap bar composition according to the invention can be a personal washing soap bar composition. In addition to the optional ingredients disclosed above, the composition for the personal washing soap bar composition may include a light-blocking agent, in which the soap bar composition is generally opaque. Examples of light-blocking agents include titanium dioxide, zinc oxide, etc. Particularly preferred light-blocking agents that can be used when an opaque soap composition is required are ethylene glycol monostearate or distearate, for example, in the form of a 20% solution in sodium lauryl ether sulfate. An optional light-blocking agent is zinc stearate.
[0099] The preferred personal washing soap composition of the present invention has a pH of 8 to 11, more preferably 9 to 11.
[0100] Preferred compositions may additionally contain up to 30% by weight of beneficial agents. Preferred beneficial agents include moisturizers, emollients, sunscreens, skin whitening agents, and anti-aging compounds. These beneficial agents may be added at appropriate steps in the manufacturing process. Some beneficial agents may be introduced as macro domains.
[0101] Soap bar composition
[0102] The laundry soap bar composition according to the present invention is a low-TFM soap bar composition with high water content. This soap bar composition maintains a high water content in the bar during storage and provides excellent hand feel, firmness, cleaning, and foaming properties. Preferably, the laundry soap bar composition of the present invention is prepared into bar form by any conventional method, including frame cooling (casting route) or milling and pressing (extrusion route). Preferably, the composition is an extruded laundry soap bar composition with high water content, which remains easy to extrude and press.
[0103] pH value:
[0104] When measured at 25°C using a 4% by weight solution in deionized water, the laundry soap bar composition according to the invention has a pH value of 9 to 13, preferably 9 to 11, more preferably 9.5 to 10.5. According to the bar composition of the first aspect, the pH value of the composition is in the range of 9 to 13 when measured at 25°C using a 4% solution in distilled water.
[0105] Total fat content:
[0106] The term "total fatty substances" or TFM is used to indicate the weight percentage of fatty acid and triglyceride residues present in the soap, excluding accompanying cations. The soap bar compositions according to the invention have a TFM content in the range of 30% to 55%, more preferably 30% to 50%, further preferably 35% to 50%, and even more preferably in the range of 40% to 55%.
[0107] shape:
[0108] The laundry soap bar composition according to the invention can be taken in any shape. The bar according to the invention has a low water loss rate, which means that the bar generally has excellent water retention and relatively low shrinkage during stamping, as well as during storage and use.
[0109] hardness:
[0110] The hardness of the laundry soap bar composition of the present invention is expressed as the force (in kg) required to move the probe a predetermined distance. Hardness is measured using a hardness tester. The bar to be tested is placed on a test platform. The probe of the measuring instrument is then placed close to the surface of the bar composition, but not in contact with it. Next, the instrument is started, the force required to reach the preset target distance is measured, and the observation results are recorded. Preferably, at a target penetration distance of approximately 10 to 40, the instrument reading is 1300 to 3000 force (R). T (in kg).
[0111] density:
[0112] The laundry soap bar composition according to the invention has a density of 0.8 to 1.3, preferably 1.01 to 1.15 g / m³. A significant advantage of the invention is that it allows for the addition of water without significantly affecting the bar density. The bar density of the invention is similar to that of conventional laundry soap bar compositions with a higher content of fatty acid soap.
[0113] Iodine value:
[0114] Preferably, the laundry soap composition according to the invention comprises soap with an iodine value in the range of 30 to 70, more preferably in the range of 30 to 60, and most preferably in the range of 35 to 45. The iodine value of the composition of the invention is measured by the Wijs 20 method, The American Oil Chemists' Society (AOCS) Official Method Cd 1-25, revised in 1988.
[0115] The iodine value is a measure of the degree of unsaturation of an oil. Also known as the iodine number, it is the amount of iodine absorbed by 100 grams of oil, fat, or wax, expressed in grams. Saturated oils, fats, and waxes do not absorb iodine; therefore, their iodine value is zero. However, unsaturated oils, fats, and waxes do absorb iodine. The more iodine absorbed, the higher the iodine value.
[0116] Method for preparing laundry soap bar composition
[0117] According to a second aspect of the present invention, a method for preparing the laundry soap bar composition of the first aspect is disclosed, comprising the following steps:
[0118] i) Neutralize one or more fatty acids or fats with an alkaline neutralizing agent to obtain fatty acid soaps;
[0119] ii) Acidify basic silicates to form silica gel in situ;
[0120] iii) Add silicate structuring agents and water to form a dough-like substance; and
[0121] iv) The resulting dough-like substance is converted into a shaped laundry soap bar composition.
[0122] The laundry soap bar composition comprises 30% to 55% by weight of fatty acid soap and 30% to 45% by weight of water, wherein the silicate structuring agent is selected from calcium silicate, aluminum silicate, sodium aluminosilicate, or mixtures thereof.
[0123] The laundry soap bar composition according to the invention can be produced on a commercial scale by any method known to those skilled in the art. Preferably, the soap bar composition of the invention is prepared using an extrusion route. Preferably, a Sigma mixer process (post-feed route) or a spiral mixer / Mazzonni / spray dryer process is used.
[0124] Neutralize fatty acids or fats to form fatty acid soaps:
[0125] The fatty acid used for neutralization can be a single type or a mixture of different fatty acids. Preferably, the fatty acid is a mixture of different fatty acids. The fats used are combinations of fats that provide preferred amounts of short-chain and long-chain fatty acid molecules. As used herein, the term fat also includes oils commonly known to those skilled in the art. The neutralization step is carried out by using an alkaline neutralizing agent to form a fatty acid soap, said neutralizing agent preferably selected from silicates, carbonates, hydroxides, alkaline aluminum-containing materials such as aluminates, phosphates, or mixtures thereof, preferably alkaline neutralizing agents are hydroxides or silicates. It is also preferred that the alkaline neutralizing agent used for neutralization is sodium hydroxide or potassium hydroxide.
[0126] Add silicate structuring agent:
[0127] The silicate structuring agent can be pre-formed or generated in situ. More preferably, the present invention relates to a method for preparing a soap bar composition according to the invention, comprising the step of generating the silicate structuring agent in situ before or after the saponification step (step i). When the silicate structuring agent is calcium silicate, it is preferably generated in situ by mixing a slightly water-soluble calcium compound with an alkali metal silicate to form calcium silicate in situ. The alkali metal silicate is preferably sodium silicate. The water solubility of the slightly water-soluble calcium compound at a temperature of 25°C is less than 2 g / L. The calcium source is preferably selected from calcium oxide, calcium hydroxide, calcium carbonate, calcium chloride, calcium sulfate, and combinations thereof. More preferably, the calcium compound is calcium hydroxide, calcium sulfate, or a mixture thereof. Preferably, the slightly water-soluble calcium compound is selected from calcium hydroxide or calcium sulfate, with calcium hydroxide being the most preferred.
[0128] Preferably, the method may include the incorporation of a further silicate structuring agent. The further silicate structuring agent refers to any additional structuring agent included besides calcium silicate, aluminum silicate, and sodium aluminosilicate. When the further silicate structuring agent is magnesium silicate, it is preferably produced in situ by mixing a magnesium source with an alkali metal silicate to form magnesium silicate in situ. The alkali metal silicate is preferably sodium silicate. The magnesium source is a magnesium compound, preferably a slightly water-soluble magnesium compound with a water solubility of less than 2 g / L at 25°C. The magnesium compound is preferably selected from magnesium oxide, magnesium hydroxide, magnesium carbonate, magnesium chloride, magnesium sulfate, and combinations thereof. Magnesium sulfate is a preferred magnesium compound.
[0129] The silicate structuring agent can be aluminum silicate or sodium aluminum silicate (also referred to herein as sodium aluminosilicate). Preferably, the in-situ generation of the aluminum silicate structuring agent is carried out by reacting a precursor material selected from (a) a soluble aluminum salt and silicate or (b) sodium aluminate and basic silicate. It is preferably generated in situ using a monomeric aluminum source condensed with a silicate anion. A preferred monomeric aluminum source is aluminum sulfate, and the silicate structuring agent is generated by reacting aluminum sulfate with basic sodium silicate to form sodium aluminosilicate in the formulation. The sodium aluminosilicate structuring agent is preferably present in an amount ranging from 0.5% to 10% by weight of the laundry soap bar composition. Preferably, the sodium aluminosilicate structuring agent can be formed in situ by reacting aluminum sulfate with an alkali metal carbonate and then with a basic silicate to form sodium aluminosilicate. Preferably, the alkali metal carbonate is sodium carbonate, and the basic silicate is sodium silicate.
[0130] In one embodiment of the invention, during the addition of the silicate structuring agent, an excess of basic silicate, preferably sodium silicate, is used in the step of forming the silicate structuring agent in situ. Subsequently, silica gel is formed in situ by reacting the remaining basic silicate with an acid.
[0131] The step of neutralizing fatty acids or fats with an alkaline neutralizing agent can be done before or after the step of forming the silicate structuring agent. Alternatively, a pre-formed soap can be added during the reaction.
[0132] Methods for in-situ preparation of silica gel:
[0133] The next step involves acidifying the basic silicate to form silica gel in situ. Preferably, the silicate is an alkali metal silicate, more preferably sodium silicate, and the acid is selected from inorganic acids (preferably sodium bicarbonate) or organic acids. Preferably, the acid is selected from carbon dioxide, organic acids, bicarbonates, or mixtures thereof. Preferably, the bicarbonate is sodium bicarbonate. In the acidification step, the desired concentration, approximately stoichiometric ratio, or a slight excess of silicate is mixed with the acid. The silicate can be added at room temperature, or it can be separately heated to a temperature in the range of about 45°C to 80°C, preferably about 60°C, prior to mixing. Preferably, silica gel is formed in situ by acidifying the basic silicate with bicarbonate. Preferably, the basic silicate is sodium silicate, and the bicarbonate is sodium bicarbonate. Preferably, the weight ratio of sodium bicarbonate to sodium silicate is in the range of 1:5 to 1:7.
[0134] Under closed container conditions, at atmospheric or near-atmospheric pressure, the reactants are simultaneously introduced into the reaction vessel and stirred to ensure homogeneity. The reaction is allowed to proceed to completion, which typically takes approximately 20 to 30 minutes. Subsequently, the pH of the silica gel is adjusted to the desired level by adding an acid or silicate. The final pH of the dough-like substance is preferably adjusted to the range of pH 7.2 to 10.0.
[0135] The preparation of the laundry soap bar composition preferably involves acidifying an excess of alkali metal silicate with an acid source selected from bicarbonates, carbon dioxide, or organic acids to form silica gel. Preferably, the bicarbonate reacts with the alkali metal silicate to form silica gel. Preferably, the bicarbonate is sodium bicarbonate, and the alkali metal silicate is sodium silicate.
[0136] In one embodiment of the invention, the steps for preparing the laundry soap bar composition include in-situ preparation of silica gel, followed by in-situ preparation of a silicate structuring agent. In this case, after the step of acidifying excess silicate with an acid (preferably bicarbonate) to form silica gel in situ, the remaining silicate is contacted with a calcium source to form calcium silicate or with an aluminum source to form sodium aluminum silicate and water to provide a dough-like substance.
[0137] Spiral mixer process:
[0138] Step (i): This is one of the well-known methods for preparing laundry soap bar compositions. In the spiral mixer process, the step of neutralizing one or more fatty acids or fats with an alkaline neutralizing agent to obtain fatty acid soaps is carried out by adding fatty acids or fats in a spiral mixer maintained at a temperature of 50°C to 90°C, wherein the fatty acids or fats have a preferred proportion range of C 12 or the following shorter-chain fatty acids and those with C 14Or longer-chain fatty acids. The oil used can be selected from distilled fatty acids or neutral oils. Next, an alkaline neutralizing agent, preferably sodium hydroxide or potassium hydroxide, is added in an amount required to achieve complete saponification of the fatty acid or fat. Afterward, the temperature of the spiral stirrer is raised to a range of 75°C to 120°C. Preferably, during the neutralization step, the required amount of sodium carbonate or sodium chloride solution is added to the neutralization mixture to obtain the fatty acid soap. Sufficient free water is added at this stage, which is required to provide the final composition having 15% to 45% water by weight. A chelating agent is added during or preferably immediately after the neutralization of the fatty acid or soap. Non-limiting examples of chelating agents include EHDP and EDTA.
[0139] Step (ii): The next step involves adding a silicate structuring agent or generating a silicate structuring agent in situ. Preferably, the silicate structuring agent is generated in situ. Preferably, the silicate structuring agent is aluminum-based. Preferably, an aluminum compound (e.g., aluminum sulfate) is added to a spiral stirrer in solid or solution form and mixed for 5 to 10 minutes to form a homogeneous mixture with the fatty acid soap. Subsequently, under ambient temperature or with slight heating before addition to the spiral stirrer, an excess of a stoichiometric amount of a basic silicate, preferably sodium silicate, is added. After addition, the contents of the spiral stirrer are mixed for about 5 to 10 minutes to allow the aluminum compound to react completely with the basic silicate to form the silicate structuring agent. As described above, preferably the aluminum compound is aluminum sulfate, and the basic silicate is sodium silicate, which react to form sodium aluminosilicate. Preferably, sodium carbonate is also present in the reaction mixture.
[0140] Step (iii): The next step involves acidifying the silicate to form silica gel in situ. First, an acid (preferably sodium bicarbonate) is added to a spiral mixer. Sodium bicarbonate is preferably in solid form. Then, an alkaline silicate is added to the mixture in stoichiometric proportions, and the clump is mixed for 5 to 10 minutes to form a dough-like substance with in-situ formed silica gel. The silica gel contains excess water.
[0141] Preferably, at this stage, the cationic polymer can be added to the dough-like substance. Adding the desired cationic polymer at the end of the process avoids the formation of any complexes with the anionic soap. Other optional ingredients that can be added to the laundry soap bar include electrolytes, dyes, acrylic polymers and colorants, glycerin, chelating agents, soluble fillers, inorganic fillers, and alkaline substances (carbonates) added to form the dough-like substance. The soap bar composition may preferably include a cationic polymer, which is preferably a homopolymer of dimethyl diallyl ammonium chloride. An example of a homopolymer of dimethyl diallyl ammonium chloride (DMDAAC) is a product sold by Lubrizol., Inc. under the registered trademark MERQUAT. Non-limiting examples include Merquat. TM100 is a highly charged cationic dimethyl diallyl ammonium chloride homopolymer. Commercially available examples of highly preferred polyquaternium-6 polymers include, for example, Merquat, available from Lubrizol. TM The polymer is 100, with a molecular weight of about 150,000 g / mol. The laundry soap bar composition according to the invention preferably contains 0.01% to 5% by weight of a cationic polymer.
[0142] At this stage, the moisture content of the dough-like substance is preferably in the range of 30 to 45% by weight.
[0143] Drying: The resulting dough-like substance is preferably dried in the next step. In this drying step, the dough-like substance is dried to reduce the moisture content of the mixture to 30% to 45% by weight. Commercially available drying steps can be achieved through several different methods. One method uses a water-cooled roller combined with a second feed roller to spread the molten neutralized soap into a thin, uniform layer. The cooled dough-like substance is then scraped off the roller to form fragments and dried to a specific moisture level in a tunnel dryer. A modern drying technique is called spray drying. This process guides the molten dough-like substance to the top of a tower through nozzles. The dough-like substance, sprayed to form a dried soap mixture, hardens and is then dried in the presence of a hot air stream. A vacuum can be applied to facilitate water removal, preferably providing a vacuum of at least 50 mmHg absolute pressure. The dried soap mixture is then extruded to form soap strips with a water content of 30% to 45% by weight. Typically, 4% to 7% by weight of moisture is removed from the dough-like substance during the drying step. Preferably, the dryer is a Mazzoni vacuum spray dryer, with the temperature maintained at 85°C to 90°C, the vacuum maintained at 700 mmHg, and the flow rate at approximately 3 to 8 tons per hour.
[0144] Pressing: Preferably, after drying, during the pressing step of the dough-like material, the dried soap strips are transferred to a pressing machine. In pressing, this step involves transforming the soap strips into a shaped laundry soap bar composition. Conventional pressing machines are set with a drum temperature of approximately 90 degrees Fahrenheit (32°C) and a die head temperature of approximately 110 degrees Fahrenheit (43°C). The pressing machine used is a two-stage twin-screw pressing machine, which allows a vacuum of approximately 40 to 65 mmHg between the two stages. Preferably, fragrance can be added at this stage. The soap strips extruded from the pressing machine are typically circular or elliptical in cross-section and are cut into individual plungers. These plungers are then preferably stamped on conventional soap stamping equipment to produce the finished shaped laundry soap bar composition. After stamping, the finished soap bars are packaged in the desired packaging material, which may be selected from laminates, films, paper, or combinations thereof.
[0145] In a preferred method, prior to pressing, the dried soap strips can undergo a combining step in a simple paddle mixer, where the strips are added to the mixer, where auxiliary ingredients such as colorants, preservatives, and fragrances are added and thoroughly mixed to combine all the ingredients. In addition, the mixture from the combiner can preferably undergo a grinding step. In a three-roll soap mill, the combined mixture is passed through rollers set to a temperature of 29°C to 41°C to obtain a homogeneous mixture; this is a close mixing step where the soap mixture is subjected to compression and strong shear. After mixing in the mill, the mixture is transferred to a pressing machine.
[0146] Sigma mixer (post-feed) process:
[0147] Another well-known method for preparing laundry soap bar compositions is known as the post-feeding process or the Sigma mixer process. The Sigma mixer process involves preparing soap bars using a spiral agitator or a plow mixer.
[0148] The step of neutralizing fatty acids or fats with an alkaline neutralizing agent is carried out in a spiral mixer or plow mixer, wherein the fatty acids or oils / fats are added together with the alkaline neutralizing agent (preferably sodium hydroxide), said fatty acids or oils / fats having a desired level of C 12 Or the following shorter-chain fatty acid molecules and C 14 The fatty acid molecules are of longer chain lengths, either 1 or 2. This step continues with the addition of sodium hydroxide until the fatty acids or fats / oils are completely neutralized. Preferably, during the neutralization step, the desired amount of sodium carbonate or sodium chloride solution is added to the neutralization mixture to obtain fatty acid soaps. Sufficient free water is added at this stage, which is necessary to provide the final composition having 30% to 45% water by weight. A chelating agent is added during or preferably immediately after the step of neutralizing the fatty acids or soaps. Non-limiting examples of chelating agents include EHDP and EDTA.
[0149] In the next step, the neutralized fatty acid soap, as described above in the spiral mixer process, is dried, preferably in a vacuum spray dryer. The resulting soap strips have a moisture content of 30% to 45% by weight.
[0150] In the next step, 30% to 55% by weight of dried fatty acid soap and the desired level of water for obtaining a final laundry strip composition having 30% to 45% by weight of water are added to a Sigma mixer, and the mixer is preferably run for 10 to 15 minutes to homogenize.
[0151] Preferably, in the next step, a silicate structuring agent and silica gel are formed as described above with reference to the spiral mixer process to form a dough-like substance. The dough-like substance then undergoes a pressing step as described above. The pressing step involves transferring the dough-like substance into a pressing machine, which includes transforming the dough-like substance into a shaped laundry soap bar composition.
[0152] According to a third aspect, the present invention discloses the use of silica gel, a silicate structuring agent and 30% to 45% by weight of water in a laundry soap bar composition having 30% to 55% by weight of fatty acid soap for providing good user performance, improved soap bar performance or foaming properties or improved fragrance delivery, wherein the silicate structuring agent is selected from calcium silicate, aluminum silicate, sodium aluminosilicate or mixtures thereof.
[0153] The invention will now be illustrated by the following non-limiting embodiments. Example
[0154] Example 1
[0155] The laundry soap bar composition according to the invention (Ex 1) was prepared using the formulation shown in Table 1. Fatty acids / fats were weighed according to the desired blend and neutralized with sodium hydroxide. Then, other cationic polymers and water, as shown in Table 1, were added, the mixture was pressed into strips, and then extruded to form a shaped laundry bar composition. Silica gel was formed in situ during the preparation of the laundry bar by reacting sodium silicate with sodium bicarbonate. The silicate structuring agent was formed in situ by mixing aluminum sulfate with sodium carbonate, and then mixing with sodium silicate to form sodium aluminosilicate.
[0156] Measurement of parameters:
[0157] a) Bar hardness
[0158] Strip hardness refers to the hardness of a strip after manufacturing, and it provides an indication of its processability, strength, and structural integrity during handling, transportation, and use.
[0159] Strip hardness was determined using the TA-XT Express Texture Analyser, which features a 30° tapered probe that penetrates the soap strip sample to a predetermined depth at a specified speed. The resistance generated at the specified depth was recorded. The strip to be tested was placed on the test platform. The probe of the measuring instrument was then placed close to the surface of the strip composition, but not in contact with it. Next, the instrument was started, the force required to reach the preset target distance was measured, and the observations were recorded (force in g, g). f ).
[0160] This value may be related to the yield stress (ref 2), which has long been considered an important determinant of processability and also related to performance in use. The hardness of freshly prepared strips and strips stored for 24 hours was measured.
[0161] b) Measure the pH value of the laundry soap bar composition.
[0162] The pH value of the laundry soap bar composition was measured at 25°C in a 4% solution of distilled water.
[0163] c) % Wear Rate Measurement:
[0164] Wear rate refers to the amount of wear and tear on a strip during use, and is measured by weight.
[0165] Step 1: Pre-treatment steps
[0166] Cut the laundry soap bar into pieces of the following size: 8.5 cm x 5 cm.
[0167] Place a damp cloth on the soap dish, place the cut soap bar with the working side facing down on the cloth, and transfer it to a sealed polyethylene bag. Let the soap bar sit undisturbed for 1 hour.
[0168] One hour later, remove the soap bars from the bag and set the soap dish aside. Immerse a 65cm x 60cm piece of cotton cloth in water with a hardness of 15FH. Once the cloth is fully soaked, remove it from the water and allow the water to drip out. Once no more water is dripping from the cloth, place it on a flat metal or plastic tray, smooth the surface, and smooth out any trapped air bubbles.
[0169] Next, remove the laundry soap bar from the soap dish and attach it to the bar holder. Now, by moving the holder from one edge of the fabric to the other in each stroke, apply the working surface of the laundry soap bar along the length of the wet fabric (60cm) to the block of wet fabric resting on a plastic or flat metal tray. Apply two such strokes so that the strokes do not overlap along the length of the wet fabric. This completes the pre-conditioning step. At this stage, measure the weight of the bar and record the weight of the bar along with the holder (W0).
[0170] Step 2: Wear Rate Assessment
[0171] After determining the weight of the strip, the working surface of the strip was rubbed again along the length of the wet cloth block in 5 non-overlapping strokes by moving the clamp from one edge of the cloth block to the other edge, covering a distance of 60 cm. After 5 strokes, the weight (W) of the strip along with the clamp was measured and recorded. The % wear rate was calculated as follows:
[0172] Weight loss over 3 meters (60 cm x 5 strokes) = W0 - W
[0173] 6. Note: For a given product, the average weight loss over five (5) times the effective fabric length corresponds to a weight loss over three meters (3 meters) – and can be expressed as the weight loss applied to every 10 meters of fabric, as follows:
[0174] 7. Weight loss per 10 meters = Weight loss over 3 meters x 10
[0175] d) Determination of soog and mush
[0176] "Softening" refers to water seeping into the strip from the air, and is related to the strip becoming wet and soft.
[0177] To measure the soft paste of the prepared laundry strip composition, the following procedure is followed.
[0178] Step 1: Pre-treatment steps
[0179] Place the cloth in a soap dish and add 10 ml of water. Then, place the laundry strip composition into the soap dish, and put the soap dish and laundry strip composition into a sealed bag. Let it sit undisturbed for 1 hour.
[0180] Step 2: Softening Assessment
[0181] At the end of 1 hour, remove the laundry soap bar composition from the sealed bag. Take a new cloth (40 cm x 25 cm) and soak it in water to moisten it. After that, remove the cloth and let it drip. Next, place the cloth on a flat surface and spread it out and flatten it. Gently wipe away any excess water. Place the pre-conditioned laundry soap bar composition in the holder at one end of the damp cloth and gently pull it to the other end of the cloth. Repeat this process twice, once on the top surface of the cloth and then on the other surface. After that, measure and record the weight of the laundry soap bar (W1). Next, put the laundry soap bar back into the soap dish and transfer it to the sealed bag, where it will stand undisturbed for 4 hours.
[0182] Step 3: Softening Assessment
[0183] Four hours later, remove the laundry soap bar from the sealed bag. Measure and record the weight of the laundry soap bar (W2). Next, gently scrape off the soft paste layer on the surface and along the sides of the soap bar with a spatula. Now, measure and record the weight of the laundry soap bar for the third time (W3). After this, leave the laundry soap bar undisturbed and visually assess for any cracks after one day.
[0184] Calculate the soft paste using the following formula.
[0185] Weight loss over 30 square centimeters = [(W1–W3)*30] / area (40 square centimeters)
[0186] The amount of soft paste on 30 square centimeters = [(W2–W3)*30] / area (40 square centimeters)
[0187] e) Measurement of foam
[0188] Soil lather refers to the foam produced during the washing process, which consumers use to control the dosage of the product.
[0189] Step 1: Pre-treatment steps
[0190] Place the cloth in a soap dish and add 10 ml of water. Then, place the laundry strip composition into the soap dish, and put the soap dish and laundry strip composition into a sealed bag. Let it sit undisturbed for 1 hour.
[0191] Step 2: Bubble Assessment
[0192] Immerse a 40cm x 25cm white towel in water with a hardness of 15FH. When it is fully soaked, remove the towel from the water and let it drip until no more water drips out. Next, place the towel on a flat metal tray, remove any wrinkles and air bubbles, and smooth the surface of the towel.
[0193] Remove the laundry strip and place the test side of the strip in the holder. Move the strip from one edge of the towel to the other edge, so that the strip covers the entire length of the towel. Repeat this process twice. The strokes do not overlap.
[0194] Next, pour 100 ml of water (15FH hardness) onto the fabric and rub the towel at each corner 8 times. Then squeeze the towel to expel all the water and foam into a measuring cylinder. Add another 20 ml of water to the towel, scrape off any remaining foam and water, and transfer it to the measuring cylinder. The amount of foam produced is calculated as follows:
[0195] Foam volume (ml) = Total volume of water and foam - Volume of water.
[0196] Let the foam stand undisturbed for 10 minutes, then recalculate and record the foam volume reading.
[0197] Table 1
[0198]
[0199]
[0200] The data in Table 1 show that laundry soap bar compositions with a low fatty acid soap content (43 wt%) and a higher than normal water content (36 wt%) provide good bar properties, such as hardness and abrasion rate, as well as good foaming properties in water at different hardness levels.
[0201] Example 2: Evaluation of the cleaning performance of the laundry soap bar composition according to the present invention.
[0202] The cleaning performance of the soap bar compositions (Ex2, Ex3) and control composition (Ex C1) according to the invention, as shown in Table 2, was evaluated using the Stain Removal Index (SRI). SRI was measured using samples with different stain types, as shown in Table 2. Measurements were performed using an FRU Precision Colorimeter WF32, which has integrated software for measuring color on the LAB scale and is equipped with a color difference for calculating CIELABΔE*, which is the difference between the stained sample and the unstained fabric. The absolute color difference is given by the following equation:
[0203]
[0204] Where L is reflectance, a is red, and b is yellow. The color difference between the stained area and the unstained fabric before washing is calculated for both the unwashed and washed stains. Based on the two values obtained, the Stain Removal Index (SRI) is calculated using the following formula.
[0205]
[0206] Here, "US" refers to the unwashed stained area, "WS" is the washed stained area, and "UF" is the unwashed unstained fabric area. ΔE (US-UF) ΔE represents the color difference between unwashed stained and unstained fabrics. (WS-UF) The SRI indicates the color difference between stained and unstained fabrics after washing. SRI is a measure of the change in stain intensity after washing, or the effectiveness of washing in removing stains. An index of 0 indicates no stain removal, while SRI = 100 corresponds to complete stain removal. The higher the SRI value, the stronger the stain removal potential. The colorimeter is used with a light source designated D65, corresponding to 6500K.
[0207] To determine the SRI, a standard protocol called the Tergometer (also known as the Tergotometer) washing protocol was used. The Tergometer washing protocol comprises the following steps: 1. Measure the color of the stain on the fabric (the unwashed stained area). 2. Turn on the Tergometer and set the temperature to 25°C. 3. Add water of the desired hardness and heat to 25°C for 10 minutes. 4. Add the preparation to each container and agitate at 100 rpm for 1 minute. 5. Add the stain sample and ballast to each container. 6. Begin washing, agitating at 100 rpm, and maintain the wash for 12 minutes. 7. Rinse with fresh water (24FH) for 2 minutes. 8. Repeat the rinsing. 9. Dry overnight in the dark. 10. Read the stain after washing.
[0208] Details of the prepared soap bar compositions and subsequent SRI studies are shown in Table 2. The silica gel in the compositions (Ex 2, Ex 3) according to the invention is prepared in situ via the reaction of sodium silicate and sodium bicarbonate. The silicate structurer in Ex 2 is sodium aluminosilicate, which is prepared in situ via the reaction of aluminum sulfate with sodium carbonate and then with sodium silicate. The silicate structurer in Ex 3 is calcium silicate, which is formed in situ via the reaction of sodium silicate with calcium silicate.
[0209] Table 2
[0210]
[0211] The data given in Table 2 show that the SRI values of compositions outside the present invention (Ex C1) are lower than those provided by compositions within the present invention (Ex 2, Ex 3). Therefore, it is demonstrated that, compared to soap bar compositions with higher soap content but lacking silicate structuring agents and silica gel, the compositions according to the present invention, with higher levels of water and lower soap concentrations, and containing a combination of silicate structuring agents and silica gel, exhibit better stain removal performance for stubborn stains (e.g., greasy stains such as red curry stains, engine oil stains, and bleachable stains such as black coffee stains).
[0212] Example 3: Evaluation of the aroma delivery performance and aroma quality of the soap bar composition according to the present invention.
[0213] A control soap bar composition (Ex C1) and compositions according to the invention (Ex2, Ex 3) with the formulations provided in Table 2 were prepared, and 0.14% by weight of citronellol fragrance was incorporated into each soap bar composition. Test fabrics were washed using each soap bar composition (Ex C1, Ex 2, Ex 3) under similar conditions. Then, a trained panel of members evaluated the fragrance performance under the following conditions: (a) fragrance delivery of the soap bar composition immediately after opening the package, (b) fragrance delivery during washing, and (c) fragrance delivery on the wet fabric after rinsing, with evaluation details shown in Table 3.
[0214] Table 3
[0215]
[0216] As can be seen from the data provided in Table 3, Ex 2 and Ex 3 have better aromatic properties compared to the comparative composition Ex C1.
[0217] Example 4: Determination of the surface properties of the soap bar composition:
[0218] Dynamic surface tension was measured at 25°C using a BP100 tensiometer (Krüss GmbH, Germany) between 10 and 50,000 ms of surface age via the maximum bubble pressure method. Values at 100 ms were selected from the kinetic curves showing surface tension versus time, as these typically correlate well with the characteristic times of air retention and bubble formation during hand washing. Dynamic surface tension, in mN / m, was recorded at 100 ms intervals.
[0219] The dynamic surface tension of the soap solution prepared using 24°FH water was recorded and is provided in Table 4 below.
[0220] Table 4
[0221] Ex C1 60 Ex 2 50 Ex 3 54
[0222] As shown in Table 4, under similar conditions, the dynamic surface tension of the aqueous solutions of the soap bar compositions (Ex 2, Ex 3) according to the present invention is lower than that of the control composition (Ex C1). The lower dynamic surface tension indicates that the soap bar compositions (Ex 2, Ex 3) according to the present invention have better cleaning effect than the control composition (Ex C1). In addition, the lower dynamic surface tension also indicates better foam volume.
Claims
1. A method for preparing a soap bar composition, the soap bar composition comprising: i) 30% to 55% by weight of fatty acid soaps; ii) 10% to 15% by weight of silica gel having a specific surface area of at least 25 square meters per gram; iii) a silicate structuring agent, wherein the silicate structuring agent is selected from calcium silicate, aluminum silicate, sodium aluminosilicate, or mixtures thereof; and iv) 30% to 45% by weight of water, The method includes the following steps: (i) Neutralize one or more fatty acids or fats with an alkaline neutralizing agent to obtain fatty acid soaps; (ii) Acidifying basic silicates with acid to form silica gel in situ; (iii) Add a pre-formed or in-situ formed silicate structuring agent and water to the fatty acid soap formed in step (i) to form a dough-like substance; and (iv) The resulting dough-like substance is converted into a shaped laundry soap bar composition. In step (ii), the alkaline silicate is sodium silicate, the acid is sodium bicarbonate, and the weight ratio of sodium bicarbonate to sodium silicate is in the range of 1:5 to 1:
7.
2. The method according to claim 1, wherein the silicate structuring agent is calcium silicate formed in situ by reacting a calcium compound with an alkaline silicate, wherein the calcium compound is selected from calcium oxide, calcium hydroxide, calcium carbonate, calcium chloride, calcium sulfate, and combinations thereof.
3. The method according to claim 2, wherein the calcium compound is calcium hydroxide, calcium sulfate, or a mixture thereof.
4. The method according to claim 1, wherein the silicate structuring agent is aluminum silicate formed in situ by reacting an aluminum compound with an alkaline silicate, wherein the aluminum compound is selected from soluble aluminum salts.
5. The method according to claim 4, wherein the aluminum compound is aluminum sulfate or sodium aluminate.
6. The method according to claim 1, wherein the silicate structuring agent is sodium aluminosilicate formed in situ by reacting an aluminum compound with an alkali metal carbonate and further with an alkaline silicate, wherein the aluminum compound is aluminum sulfate and the alkali metal carbonate is sodium carbonate.
7. The method according to any one of claims 2-6, wherein the alkaline silicate is sodium silicate.
Citation Information
Patent Citations
Sounding lines
GB209013A
Soap-based laundry bars with improved firmness
WO1996035772A1
Process for manufacture of non-granular solid detergent composition
WO2002046341A2
Detergent bar composition and process for its manufacture
WO2003040283A1
Process to prepare a soap bar
WO2008071561A1